Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages From the middle of 1917, the cases occurring decreased rapidly, although about 50,000 workers were still working with T.N.T. It was never proved conclusively whether it was most dangerous to breathe in the dust or to rub it into the skin. Some of the investigators, notably Dr Moore, thought that it was most dangerous to absorb T.N.T. through the skin; others remained convinced until the end of the war, and still think to-day, that it was dangerous to absorb T.N.T. through the mouth and nose as well as through the skin. The most energetic measures on record in the last war against absorption were taken at the Scottish Filling Factory, Georgetown. In the last year it was operating, with Dr Elizabeth Butler as the Senior Medical Officer, no single case of T.N.T. poisoning occurred among the workers. This is to be regarded as a remarkable achievement of preventive medicine. In this war, figures of T.N.T. poisoning have not been published, but cases are occurring again and doctors are writing articles about them in the Medical Press, and Dr Bridge, Senior Medical Inspector of Factories, admits it in his Annual Report, 1940. The Lancet, in a leader on November 15, 1941, writes "Many are asking, as Edward VII asked about Tuberculosis, 'if preventible [preventable], why not prevented'." The symptoms of T.N.T. poisoning may be mild or serious. Hands get stained and more rarely there is some staining of the face and hair; it is not so marked as the staining from C.E. (Tetryl). Where the powder contacts the hands there may be a dermatitis, i.e., an inflammation of the skin. Sago grain eruptions start between the fingers which itch very much. A red rash may occur on the neck, wrist, and ankles as well, probably from dusty clothing rubbing the skin. Cases of dermatitis need to be removed from contact with T.N.T., but can go back to that work on recovery. Cases that relapse should probably keep away for good. Dermatitis alone is not a serious symptom. T.N.T. has a more serious effect on the blood, changing the nature of the red oxyhaemoglobin in the blood cells. When this happens, workers look slightly blue; lips, tongue, and the mucous membranes become a greyish purple colour. Mild degrees are of little importance, but cases need watching carefully, as the blood changes may become serious. T.N.T. also causes a gastritis. This is evidenced by a pain in the middle of the abdomen and a feeling of sickness, or actual vomiting. It is often accompanied by a tight feeling in the chest, 28 21/2049